SMEs sustainability through entrepreneurship training in Tanzania - Mrisho Mbegu Malipula (Journal of Enterprise and Development (JED), 2023)
Purpose — The research uncovers how entrepreneurship training impacts SMEs sustainability, outlines relevant training, exposes the limitations to accessing such training in Tanzania, and recommends strategies to improve access.Method — This article reports on a qualitative case study conducted in Morogoro Municipality from 2021 to 2022. The study involved 62 face-to-face interviews with entrepreneurs in Sabasaba, Mazimbu, and Kihonda Wards, as well as KIIs with five government officials dealing with entrepreneurship matters. These Wards were selected because of their high numbers of SMEs and economic potential. The data obtained from interviews and desk reviews were analyzed through content analysis and presented descriptively, with triangulation applied to ensure data validity and reliability. Documentary reviews were used to complement the data.Result — The study supports previous research suggesting that entrepreneurship training has a positive impact on the sustainability of SMEs. Specifically, training in customer service, opportunity identification, and record keeping were seen as crucial for increasing customers, sales, and profits, ultimately leading to SME sustainability. However, the high costs associated with such training prevent many entrepreneurs from accessing it. Therefore, interventions from government and other authorities are necessary to make relevant entrepreneurship training more accessible and affordable.Contribution — This article confirms the positive link between entrepreneurship training and SMEs sustainability using empirical evidence from Tanzania. It identifies specific trainings that can enhance SMEs sustainability, obstacles to accessing training, and suggests practical interventions and policies to improve training accessibility.